Neurocognitive impairment in females with breast cancer treated with endocrine therapy and CDK4/6 inhibitors: a pharmacovigilance study using the World Health Organization’s database - Prevost, Rachel; Chretien, Basile; Minoc, Elise-Marie; Dolladille, Charles; Da-Silva, Angélique; Nehme, Ahmad; Joly, Florence; Lelong-Boulouard, Véronique; Bastien, Etienne (Frontiers in Pharmacology, 2023)
Importance: Endocrine therapies (ETs) and inhibitors of cyclin-dependent kinases-4/6 (iCDK4/6s) are a standard treatment in breast cancer. However, data on potential neurocognitive impacts remain inconsistent for ET and are scarce for iCDK4/6s. Objective: To evaluate whether ET and iCDK4/6s are associated with neurocognitive impairment (NCI). Methods: We used observational, real-world cases of NCI from the World Health Organization’s database VigiBase® to perform disproportionality analysis. Cases were defined as any symptom of NCI in females treated with ETs or iCDK4/6s. The study period was from the date of the first adverse event reported in VigiBase® with iCDK4/6s (1 January 2014) until the date of data extraction (16 March 2022). In our primary analysis, we calculated the reporting odds ratio (ROR) adjusted for age to identify a potential association between NCI and individual ETs in isolation or in combination with iCDK4/6s. We also performed subgroup analyses by the NCI class. Results: We identified 2.582 and 1.943 reports of NCI associated with ETs and iCDK4/6s, respectively. NCI was significantly associated with each ET [anastrozole: n = 405, aROR = 1.52 (95% CI: 1.37–1.67); letrozole: n = 741, aROR = 1.37 (95% CI: 1.27–1.47); exemestane: n = 316, aROR = 1.37 (95% CI: 1.22–1.53); tamoxifen: n = 311, aROR = 1.25 (95% CI: 1.12–1.40); and fulvestrant: n = 319, aROR = 1.19 (95% CI: 1.06–1.33)] and only with palbociclib for iCDK4/6s [n = 1,542, aROR = 1.41 (95% CI: 1.34–1.48)]. Conclusion: These findings suggest that in females treated for breast cancer, all ETs may be associated with NCI. However, amongst iCDK4/6s, NCI may be specific to palbociclib. NCI most frequently involved learning and memory as well as language. Neurocognitive impact of treatments requires better consideration and management.